Exploring Professional Boundaries: A Shift to Inter-Professional Early Childhood Intervention Practice in Lithuania - Ališauskiene, Stefanija; Gevorgianiene, Violeta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
A vast body of literature is focusing on the interdisciplinary approach in the field of early childhood intervention (ECI) practice, however inter-professional relations challenge traditional understanding of professional role and identity. The article contributes to the discussion about the value and the pitfalls of inter-professional cooperation in the field of ECI and its possible effects on family and child life. The aim of the research was to explore what competences professionals representing different fields perceive as most important for successful inter-professional collaboration. The study was based on experts’ evaluation (questionnaire). An analysis of the data revealed the importance professionals allocated to opinion-sharing in the emerging early childhood intervention inter-professional teams as well as a lack of attention to the parents’ voice, which indicates the need for further cohesiveness – a shift from a polylogue of different disciplines to an inter-professional culture.